KEKOMUTATIFAN PADA GRUP PERMUTASI - Newton . (Jurnal Matematika UNAND, 2013)
Some research about cycle permutations and disjoints on cycle nonemptysets has been posted in some papers. However, the degree of the generalization of thisresult is varies. In this paper we studied the notion disjoint to be applied in arbitrarycollections of permutations on arbitrary nonempty sets.